ANALISA SEBARAN ILUMINASI CAHAYA PETROMAKS DENGAN PERLAKUAN BERTUDUNG DAN TANPA TUDUNG - Patty, Wilhelmina (Sam Ratulangi University, 2010)
Petromaks lights are often used by fishermen as fishing tools. Transmitting light petromaks much influenced by various factors such as fading (attenuation). The purpose of this paper is to understand the distribution of light transmitting petromaks and factors influencing it. The result showed that the illumination of light shade petromaks which light transmitting distance range further (± 8 m) than petromaks lights that are not covered (± 21 m). The constant fading (attenuation) of light is also greater (0.78) for light petromaks hooded lamp from the lamp to petromaks without hood (0:24).